2005
DOI: 10.1016/j.cardiores.2005.01.025
|View full text |Cite
|
Sign up to set email alerts
|

G-protein-coupled receptor kinase activity in human heart failure: Effects of β-adrenoceptor blockade

Abstract: According to our results, an increase in GRK activity is an early and transient event in the course of heart failure that can be prevented by beta-adrenoceptor blocker treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 30 publications
1
37
0
1
Order By: Relevance
“…As discussed above, in CHF, sympathetic activity is increased; accordingly, it could be expected that activity of GRK2 is increased. This has in fact been shown for cardiac GRK in patients with end-stage heart failure (Ungerer et al 1993;Leineweber et al 2003Leineweber et al , 2005. Studies, mainly in transgenic mice, have shown that such an increase in the activity of GRK2 is obviously associated with a decrease in contractile force, and this can be restored by inhibition of GRK2 (Hata et al 2004).…”
Section: Effects On Force-frequency Relationshipmentioning
confidence: 84%
See 1 more Smart Citation
“…As discussed above, in CHF, sympathetic activity is increased; accordingly, it could be expected that activity of GRK2 is increased. This has in fact been shown for cardiac GRK in patients with end-stage heart failure (Ungerer et al 1993;Leineweber et al 2003Leineweber et al , 2005. Studies, mainly in transgenic mice, have shown that such an increase in the activity of GRK2 is obviously associated with a decrease in contractile force, and this can be restored by inhibition of GRK2 (Hata et al 2004).…”
Section: Effects On Force-frequency Relationshipmentioning
confidence: 84%
“…Numbers at the bottom of the column number of patients studied. Modified from Leineweber et al (2005) "loss-of-function" polymorphism with the Arg389 β-1 AR exhibiting a three-to fourfold higher isoprenaline-stimulated adenylyl cyclase activity than the Gly389 β-1 AR variant due to a better coupling of the Arg389 to G s -protein than the Gly389 β-1 AR variant (for recent reviews, see Small et al 2003;Leineweber et al 2004;Kirstein and Insel 2004;Brodde et al 2006).…”
Section: Possible Role Of β-1 Adrenoceptor Polymorphismsmentioning
confidence: 99%
“…It has been reported [43] that in these patients the expression of β1-AR is reduced at the mRNA and protein level. In addition, the expression of the inhibitory G-protein Gi is found to be increased [43]. In addition, in HF patients the expression of GRK is elevated and it is upregulated [10,44].…”
Section: G Protein Related Kinases -General Overviewmentioning
confidence: 94%
“…In patients with dilated cardiomyopathy β-AR responsiveness of the myo cardium is diminished [42]. It has been reported [43] that in these patients the expression of β1-AR is reduced at the mRNA and protein level. In addition, the expression of the inhibitory G-protein Gi is found to be increased [43].…”
Section: G Protein Related Kinases -General Overviewmentioning
confidence: 99%
“…This is because of the fact that b-blockers cause the upregulation of cardiac bARs (which are downregulated in HF) as well as the normalization of both Gi-protein activity and GRK activity (which are enhanced in HF). 35 Therefore, in situations when catecholamines overcome the b-blocker (that is, exercise), cardiac bAR signaling is improved, which can contribute to less SNS activity, thus breaking the vicious cycle indirectly (see below). Importantly, these molecular effects are associated with improved hemodynamics and overall cardiac performance.…”
Section: B-blockers: a Solid Rock In Hf Treatmentmentioning
confidence: 99%